Bioroute Production Of Biodiesel Using Cerbera Odollam Oil In Packed Bed Reactor - Rahman, Siti Norrahmah Ab (2011)
Diminishing reserves of fossil fuels and arising of food crisis recently have drawn attention for researchers to produce an alternative fuels. Biodiesel which is made from vegetable oils, animal fats or microbial oils is one of the attractive alternative fuels due to this concern. Other than that, biodiesel is an environmental friendly fuel which emitted less greenhouse effect gas. Cerbera odollam oil was determined as a non-edible feedstock for biodiesel production. The enzymatic transesterification of Cerbera odollam oil as a feedstock has been studied in the present research. Cerbera odollam oil has been extracted using n-hexane solvent in a soxhlet extractor. The enzymatic transesterification were carried out in a batch system to screen the most efficient enzyme among Lipozyme RM IM, Lipozyme TL IM and Novozyme 435 based on the highest fatty acid methyl ester (FAME) yield in the process. The best organic solvent used in this reaction was also determined in a batch process between tert-butanol and n-hexane to eliminate the inhibition of methanol in the reaction. Important parameters like temperature, speed agitation, enzyme concentration, methanol to oil ratio and solvent to oil ratio in enzymatic transesterification reaction were optimized by using response surface methodology (RSM) based on central composite design (CCD). The kinetic studies of enzymatic tansesterification were carried out in this research. Enzymatic transesterification of Cerbera odollam oil reaction was also studied in a packed bed reactor (PBR) for a continuous process. The effect of mass transfer in the PBR was also studied.